The State Administrative Decision-Making in the Adoption of Maslahah Mursallah Principle in Indonesia - Efik Yusdiansyah (Sriwijaya Law Review, 2023)
The development of State Administration Law is a prerequisite for constitutional development in realising good governance. From the perspective of national administration, administrative reform is a revision of several legal policies related to structure, process, and management in the areas of finance, supervision, staffing, accountability and transparency, and political decision-making processes and their implementation. Political decision-making process and its implementation. State administration reform also means reform in the field of state administration law. As one of the efforts to use the Islamic Law approach, one of which is the principle of maslahah mursalah, which prioritises the benefit of the people. So what if this principle is applied to policy making by State Administrative Officials. This study aims to determine the application of the principle of maslahah mursalah to State Administrative Decisions. The method used is normative legal research method, using deductive analysis method. It is hoped that the results of this research will be able to provide an overview of the role of the maslahah mursalah principle in efforts to realise State Administrative Decisions based on good values, as well as providing a sense of justice and prioritising benefits and avoiding mischief.